2021
DOI: 10.21203/rs.3.rs-183425/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of unipolar and bipolar hemiarthroplasty for femoral neck fractures

Abstract: Background Femoral neck fracture is a common fracture in the elderly. Improper treatment seriously impacts the patient and could potentially shorten their lifespan. Hemi-arthroplasty is a common treatment for femoral neck fractures, but the selection of unipolar prosthesis or bipolar prosthesis is still a controversial issue. Therefore, we conducted this comprehensive meta-analysis to compare the outcomes of unipolar and bipolar prostheses. Methods We searched the PubMed, EMbase, The Cochrane Library, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, the most recent meta-analysis combining eight studies (cohort studies and RCTs) found no significant difference in HHS score at last follow-up between the use of UH and BH. 24…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the most recent meta-analysis combining eight studies (cohort studies and RCTs) found no significant difference in HHS score at last follow-up between the use of UH and BH. 24…”
Section: Discussionmentioning
confidence: 99%
“…The intraprosthetic motion between the inner and outer shell in bipolar heads could potentially shield the acetabulum from erosion and wear. Dong et al 24 combined six studies totalling 503 cases, and found an acetabular erosion rate five-times higher in UH compared to BH. Fillippo et al 25 combined 16 studies and found a statistically significant reduction in acetabular erosion in the bipolar group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation